2015
DOI: 10.1038/cdd.2015.126
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death 50 (and beyond)

Abstract: In the 50 years since we described cell death as 'programmed,' we have come far, thanks to the efforts of many brilliant researchers, and we now understand the mechanics, the biochemistry, and the genetics of many of the ways in which cells can die. This knowledge gives us the resources to alter the fates of many cells. However, not all cells respond similarly to the same stimulus, in either sensitivity to the stimulus or timing of the response. Cells prevented from dying through one pathway may survive, survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 73 publications
2
24
0
2
Order By: Relevance
“…In normal cells, the onset of moderate autophagy usually inhibits the occurrence of apoptosis [39]. However, excessive autophagy in cells stimulated by drugs and other factors may play an important role in apoptosis [40, 41]. In the present study, we found that both apoptosis and autophagy were induced after isogambogenic acid treatment.…”
Section: Discussionsupporting
confidence: 59%
“…In normal cells, the onset of moderate autophagy usually inhibits the occurrence of apoptosis [39]. However, excessive autophagy in cells stimulated by drugs and other factors may play an important role in apoptosis [40, 41]. In the present study, we found that both apoptosis and autophagy were induced after isogambogenic acid treatment.…”
Section: Discussionsupporting
confidence: 59%
“…Various cell death events have been described at the cellular level dating as far back as the late 19th century [reviewed in ]. The knowledge that cell death is a regulated process did not emerge until the latter half of the 20th century, and it was not until the beginning of the 21st century that the existence and physiological relevance of non‐apoptotic cell death was formally recognized . Within this context, it seems likely that our understanding of ferroptosis and other forms of cell sabotage is incomplete and that further evidence could be adduced that these processes represent adaptive features of biological systems.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of proteasome immune subunits influences the activation of macrophages and their polarization into either an ED1- or ED2-phenotype [ 45 ]. Therefore, the change in LMP2 and LMP7 subunit levels in cell subpopulations can be associated with the activation of macrophages type 2.…”
Section: Resultsmentioning
confidence: 99%